2018
DOI: 10.4038/jas.v13i3.8399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fertilizers on Crop Growth, Oil yield and Chemical Composition of Lemongrass (Cymbopogon citrates (DC.) Stapf)

Abstract: Purpose: Lemongrass (Cymbopogan citrates (DC) Stapf. ) is ranked among the top ten oil bearing crops in the world and the essential oils of lemongrass are widely used in pharmaceutical, cosmetics, food and fl avor, agriculture industries and possess an array of medicinal uses. Aromatic grasses respond well to application of manures and fertilizers. However, farmers do not use fertilizer. Therefore, it is very important to fi nd out the possibility to increase oil yield and improve the quality of essential oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
1
5
2
Order By: Relevance
“…An increase in leaf growth rate was also observed in another study conducted on the effect of fertilizers on the growth of the lemon grass. 29 Premathilake et al reported leaf numbers no higher than 65 leaves per plant at month 3 of their experiment with both the chemical and compost fertilizer used while at month 3 (12 weeks) of our experiment, the highest leaf number was 190 with respect to the 5.5 L m −2 digestate concentration and 60 for the lowest concentration of 0.6 L m −2 used. This could possibly be due to several parameters such as lower concentrations of nutrients in the fertilizers used in their study, the quality and nutrient content of digestate, levels of sunlight and air quality.…”
Section: Effect Of Digestate Tea On Leaf Productioncontrasting
confidence: 48%
See 4 more Smart Citations
“…An increase in leaf growth rate was also observed in another study conducted on the effect of fertilizers on the growth of the lemon grass. 29 Premathilake et al reported leaf numbers no higher than 65 leaves per plant at month 3 of their experiment with both the chemical and compost fertilizer used while at month 3 (12 weeks) of our experiment, the highest leaf number was 190 with respect to the 5.5 L m −2 digestate concentration and 60 for the lowest concentration of 0.6 L m −2 used. This could possibly be due to several parameters such as lower concentrations of nutrients in the fertilizers used in their study, the quality and nutrient content of digestate, levels of sunlight and air quality.…”
Section: Effect Of Digestate Tea On Leaf Productioncontrasting
confidence: 48%
“…Furthermore, there was also no significant difference in the overall plant heights at the end of their 6 month experiment. 29 The results observed in our study can possibly be attributed to the supply of nutrients to the plants as provided by the digestate tea, where an increase in the nutrient supply resulted in an increase in growth rate. Increasing the amount of digestate tea beyond the 0.6 L m −2 application does not result in any further increase in the height of the plants as indicated in Fig.…”
Section: Effect Of Digestate Tea On Plant Heightmentioning
confidence: 53%
See 3 more Smart Citations